PREVALENCE OF MULTIDRUG RESISTANT ESCHERICHIA COLI AND KLEBSIELLA PNEUMONIAE SPECIES ISOLATED FROM URINE SAMPLES OF PATIENTS AT ALEX EKWUEME FEDERAL UNIVERSITY TEACHING HOSPITAL ABAKALIKI, EBONYI STATE, NIGERIA - Chinaemerem, Onu Henrietta; Alexander, Idoko; Romanus, Iroha Ifeanyichukwu (Universal Journal of Pharmaceutical Research, 2023)
Aim and Objective: In hospitals and community, morbidity and mortality are attributed to urinary tract infections (UTIs). This study investigated the prevalence of multi-drug resistant isolates of Escherichia coli and Klebsiella species from urine samples of patients visiting Alex Ekwueme Federal University Teaching Hospital Abakaliki (AE-FUTHA), Ebonyi State. Method: With the use of standard microbiological and biochemical techniques for analysis, a total of 300 mid-stream samples of urine were collected in sterile bottles. Phynotype screening for extended spectrum beta lactamase (ESBL) production was achieved by double disc synergy test (DDST). Disc diffusion method was used to check for ESBL producing bacteria susceptible to antibiotics. With specific primers, the presence of temoniera (TEM) and sulfhydryl variable (SHV) beta lactamases genes was determined using polymerase chain reaction (PCR). Results: 88 isolates of E coli and Klebsiella species were isolated from the urine samples; 29 were E coli and 59 were K. pneumonia species. 47 ESBL positive isolates were identified with E. coli, 19 (40%) and Klebsiella, 28 (60%). Escherichia coli isolated from GOPD patients, gynecology, and men’s surgery ward were 100% resistant to ofloxacin, ceftazidime, amoxicillin, nitrofurantoin, chloramphenicol, and aztreonam, while Klebsiella species isolated from gynecology department, maternity ward, and psychiatric ward were 100% resistant to ofloxacin, Nitrofurantoin and chloramphenicol. Multiple antibiotics resistance index (MARI) of E. coli and Klebsiella species isolated recorded an average of 0.64 for E. coli and 0.41 for Klebsiella species.The molecular analysis revealed that 44.4% of SHV beta lactamase and 65.6% TEM-type β-lactamase genes were present in ESBL producing E. coli while 54.5% of SHV beta lactamase gene and 45.5% TEM-type β-lactamase genes were present in ESBL producing Klebsiella species. Conlusion: In conclusion, TEM and SHV-type β-lactamase genes are the primary cause of β-lactam antibiotic resistance in E. Coli and Klebsiella species resulting in increased infections caused by organisms harboring the ESBL gene. Nitrofurantoin, ceftazidime, cefalexin, and cefotaxime may be the antibiotic of choice in the treatment of UTIs. Peer Review History: Received: 3 December 2022; Revised: 9 January; Accepted: 24 February 2023; Available online: 15 March 2023 Academic Editor: Dr. Amany Mohamed Alboghdadly , Princess Nourah bint abdulrahman university, Riyadh, amalbgadley@pnu.edu.sa Reviewers: Prof. Hassan A.H. Al-Shamahy, Sana’a University, Yemen, shmahe@yemen.net.ye Dr. Tamer Elhabibi, Suez Canal University, Egypt, tamer_hassan@pharm.suez.edu.eg